A green and environmentally friendly oil-water separation membrane and its preparation method and application
A lignin-modified cotton membrane with ethyl cellulose enhances mechanical properties and hydrophobicity, addressing environmental concerns and improving separation efficiency and adsorption capacity for oily wastewater.
Patent Information
- Application Number
- CN202411223071.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-03
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2044-09-03
AI Technical Summary
Existing oil-water separation materials are often prepared with non-renewable raw materials, leading to environmental pollution and have limitations in mechanical properties, adsorption capacity, and separation efficiency, while biodegradable options like cellulose-based membranes face complex synthesis processes and poor performance.
A method involving amination of lignin and immersion of cotton substrates in aminated lignin and ethyl cellulose solutions to create a membrane with enhanced mechanical properties and hydrophobicity, using renewable biomass resources.
The resulting membrane achieves high separation efficiency (up to 98%) and adsorption capacity (up to 23.7 g/g) with recyclability and reduced environmental impact, suitable for oily wastewater treatment.
Smart Images

Figure CN118718766B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to renewable energy utilization technology and oil-water separation technology, and in particular to a green and environmentally friendly oil-water separation membrane and a preparation method and application thereof. Background Art
[0002] In recent years, oil spills and oily wastewater discharges have become a serious threat to ecosystems and environmental sustainability. Many methods have been developed to eliminate the threat of oily wastewater, such as precipitation, combustion, separation, and biodegradation. However, these methods have disadvantages such as low removal efficiency, high cost, and secondary pollution, which greatly limit their practical applications. With the development of nanoscience and nanomaterials, many biomimetic materials with special wettability have attracted increasing attention, including two-dimensional fiber membranes and three-dimensional porous materials. Compared with 2D fiber membranes with high permeation flux and oil-water separation efficiency, hydrophobic 3D porous materials have the characteristics of large oil absorption capacity, low cost, and simple working equipment, and seem to have greater industrial potential.
[0003] At present, oil-water separation materials are divided into adsorption type and filtration type according to the oil-water separation method, and the filtration type oil-water separation membrane is divided into super hydrophobic / super oleophilic (SHB / SOL), super hydrophilic / super oleophobic and super hydrophilic / super oleophilic according to its wettability. Among them, super hydrophobic / super oleophilic membrane can filter water in oil-water mixture, and is more suitable for the separation of crude oil and water mixture with large viscosity and density. Due to the large molecular weight and high viscosity of heavy oil, SHB / SOL materials have greater application advantages in oil-water separation. However, traditional oil-water separation materials are prepared with part or all of non-renewable raw materials. After being discarded, it not only increases resource consumption, but also causes new environmental pollution.
[0004] In the prior art, CN107812453A discloses a method for preparing a biodegradable oil-water separation membrane for multifunctional applications, wherein the method for preparing the oil-water separation membrane is as follows: after activating the polymer body, a nanofiber membrane is prepared by electrospinning, and then the nanofiber membrane is dried and immersed in a nitrogen-containing mixed solution of a TiO2 precursor for hydrothermal reaction to obtain a biodegradable oil-water separation membrane, wherein the polymer may be lignin. The above-mentioned oil-water separation membrane is based on cellulose as a matrix material, and has the functions of being renewable and biodegradable, but its synthesis process is complex and its adsorption capacity is poor. The paper "Study on Efficient Separation, Amination Modification of Lignin and Antifouling Performance of Polyethersulfone Membrane" (Peng Meijiao, Guangxi University, 2023) discloses that aminated lignin is dissolved in NMP, and then polyethersulfone is added to mix, and an AML / PES composite membrane is prepared by solvent / non-solvent exchange and phase inversion. The AML / PES composite membrane can be used for oil-water separation, and the hydrophilicity of the composite membrane is improved by blending aminated lignin with polyethersulfone particles. The above membrane has good antifouling properties, but the polyethersulfone membrane is difficult to degrade, which limits its application to a certain extent.
[0005] Therefore, it is necessary to prepare a separation membrane with good mechanical properties and selective wettability, which can improve the oil-water separation efficiency and the adsorption capacity of oil and fat when used for oil-water separation in oily wastewater. Summary of the invention
[0006] In view of the above-mentioned prior art, the purpose of the present invention is to provide an oil-water separation membrane and a preparation method thereof. The present invention first performs an amination treatment on lignin through a Mannich reaction to obtain aminated lignin, and then immerses a cotton substrate in an alkali solution containing aminated lignin to obtain lignin-modified cotton, which is then immersed in an ethyl cellulose solution to obtain an oil-water separation membrane. The present invention constructs a stable selective wettability self-cleaning surface under the force of chemical bonding. Among them, cotton fiber can improve the mechanical properties of the membrane, aminated lignin can introduce nanoparticles, and ethyl cellulose can reduce the surface energy of the membrane and improve the hydrophobic properties of the membrane. The present invention uses biomass resources to replace artificial synthetic polymer materials, and the obtained separation membrane can be self-degraded, ensuring the environmental protection and anti-pollution properties of the membrane.
[0007] To achieve the above object, the present invention adopts the following technical solution:
[0008] A first aspect of the present invention provides a method for preparing an oil-water separation membrane, comprising the following steps:
[0009] (1) dissolving aminated lignin in an alkaline solution to obtain an aminated lignin solution; soaking the pretreated cotton substrate in the aminated lignin solution and then drying the substrate to obtain lignin-modified cotton;
[0010] (2) Dissolving ethyl cellulose in an ethanol solution to obtain an ethyl cellulose solution; soaking the lignin-modified cotton in the ethyl cellulose solution and then drying it to obtain an oil-water separation membrane.
[0011] Preferably, in step (1), the preparation method of aminated lignin is: dissolving lignin in a NaOH solution to obtain a lignin solution; adding ethylenediamine to the lignin solution to obtain a mixed solution, heating the mixed solution to 70-90° C. and keeping the temperature, then adding formaldehyde solution to the mixed solution, reacting at 70-90° C., and precipitating the reaction product with hydrochloric acid to obtain aminated lignin.
[0012] More preferably, the solid-liquid ratio of lignin to NaOH solution is (0.3-0.6) g: 25 mL.
[0013] More preferably, the pH of the NaOH solution is 10-11.
[0014] More preferably, the solid-liquid ratio of lignin, ethylenediamine and formaldehyde solution is (0.3-0.6) g: 1 g: 0.5 mL.
[0015] Further preferably, the mass fraction of the formaldehyde solution is 35-40%.
[0016] More preferably, the reaction time is 0.3-0.6h.
[0017] Further preferably, the reaction product is precipitated with 10% by mass hydrochloric acid and then centrifuged to obtain aminated lignin.
[0018] Preferably, in step (1), the alkaline solution is a NaOH solution, and the pH of the NaOH solution is 10-11.
[0019] Preferably, in step (1), the solid-liquid ratio of aminated lignin to alkaline solution is 0.5 g: (20-30) mL.
[0020] Preferably, in step (1), the soaking time is 0.3-0.6 h and the drying temperature is 50-80°C.
[0021] Preferably, in step (1), the cotton substrate is pretreated by washing the cotton substrate with deionized water and ethanol in sequence to remove dust and impurities on its surface, and then drying the washed cotton substrate at 50-80°C.
[0022] Preferably, in step (1), the cotton substrate is cotton or cotton fabric.
[0023] Preferably, in step (2), the solid-liquid ratio of ethyl cellulose to ethanol solution is (0.05-0.15) g: 10 mL.
[0024] Preferably, in step (2), the volume fraction of the ethanol solution is 75%.
[0025] Preferably, in step (2), the soaking time is 0.3-0.6 h and the drying temperature is 50-80°C.
[0026] The second aspect of the present invention provides an oil-water separation membrane prepared by the above method.
[0027] The third aspect of the present invention provides the use of an oil-water separation membrane in separating oily wastewater.
[0028] Preferably, the oil in the oily wastewater is one or more of n-butane, chloroform, soybean oil or olive oil.
[0029] Beneficial effects of the present invention:
[0030] The invention obtains aminated lignin by amination treatment of lignin, and then sequentially immerses a cotton substrate in an aminated lignin solution and an ethyl cellulose solution to obtain an oil-water separation membrane. The oil-water separation membrane uses cotton fiber as a substrate, lignin and ethyl cellulose as modified materials, and can achieve a separation rate of more than 98% for two-phase oily wastewater.
[0031] Among them, using cotton fiber as a substrate can improve the flexibility, mechanical properties and rapid oil droplet adsorption of the separation membrane. Compared with foam and aerogel substrates, it has longer cycle performance and service life, and is also a hydrogen bond donor. After the lignin undergoes a Mannich reaction, it is connected to the amino group to improve its own activity. At the same time, the introduction of micro-nano particles provides technical support for the construction of surface micromorphology. Ethyl cellulose has a lower surface energy, which can reduce the surface energy of the oil-water separation membrane, making it impossible for water droplets with high surface energy to spread on its surface, so that the oil-water separation membrane exhibits hydrophobic properties. It can also form hydrogen bonds with cotton fibers to improve the mechanical properties of the oil-water separation membrane.
[0032] The present invention uses renewable energy as a driving force from the selection of raw materials to the process of achieving oil-water separation. Compared with traditional separation membranes, it can achieve a large amount of carbon reduction. The present invention also effectively solves the self-degradability of the separation membrane and effectively prevents the "secondary pollution" problem that occurs during use. At the same time, the oil-water separation membrane prepared by the present invention not only has enhanced adsorption of grease, but the adsorbed grease can also be recovered by extrusion or peristaltic pump to achieve the reuse of grease. The preparation method of the green and environmentally friendly separation membrane provided by the present invention is simple, and the membrane structure is controllable. The prepared oil-water separation membrane is suitable for the treatment of oily wastewater generated in various production fields, and is particularly suitable for the separation of two-phase oily wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] Figure 1: (a) Scanning electron micrograph of cotton in Example 1; (b) Scanning electron micrograph of lignin-modified cotton in Example 1; (c) Scanning electron micrograph of the oil-water separation membrane in Example 1;
[0034] Figure 2 : Change in wettability of the oil-water separation membrane prepared in Example 1 after 50 cycles;
[0035] Figure 3 : Change in separation efficiency of the oil-water separation membrane prepared in Example 1 after 10 cycles; DETAILED DESCRIPTION
[0036] It should be noted that the following detailed descriptions are illustrative and are intended to provide further explanation of the present application. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present application belongs.
[0037] Most oil-water separation materials are partially or completely prepared from non-renewable raw materials during the preparation process, and the obtained oil-water separation materials are often non-degradable, causing a certain environmental burden. In the prior art, although cellulose is publicly used as a base material and modified by lignin, etc. to obtain a renewable and degradable oil-water separation membrane, there are problems such as complex preparation process and poor adsorption capacity of the obtained oil-water separation membrane.
[0038] Based on this, the present invention provides an oil-water separation membrane and its preparation method and application. The preparation method of the oil-water separation membrane is: soaking a cotton substrate in an aminated lignin solution and an ethyl cellulose solution in sequence, taking it out and drying it, and then obtaining the oil-water separation membrane. The oil-water separation membrane has a hydrophobic-lipophilic property. When it is used for oil-water separation of an oil-water mixture containing chloroform, its separation efficiency can reach 98.34%. At the same time, it shows good adsorption effects on n-butane, chloroform, soybean oil and olive oil, and the maximum adsorption amount can reach 23.7g / g.
[0039] Cotton is one of the main crops with low production cost and high yield. The microfibrils on the surface are arranged in a spiral structure. This special micro-spiral structure gives it excellent mechanical properties and endows cotton with extraordinary water / oil collection ability. Cotton will be biodegraded in most natural environments. Based on this, the present invention uses green cotton fiber as a separation membrane matrix, introduces ethyl in ethyl cellulose to complete the surface low surface energy modification and highly active aminated lignin particles to modify the surface roughness to prepare a green and environmentally friendly oil-water separation membrane.
[0040] The present invention improves the stability and mechanical properties of the oil-water separation membrane by chemical cross-linking. Specifically, ethyl cellulose with an ethoxy content of 48% is used, and hydroxyl groups exist in the main chain of the ethyl cellulose. Aminated lignin has amino groups at the end. Under alkaline conditions, the ethyl cellulose is bridged with the lignin molecular chain through hydrogen bonds. The amino groups and ether bonds can produce various chemical interactions with the ethyl cellulose material, mainly hydrogen bonds, thereby improving the adhesion of the hydrophobic layer on the substrate. At the same time, compared with lignin, the presence of amino groups in the aminated lignin improves its own activity, and micro-nano particles are also introduced to improve the hydrophobic properties of the membrane. Ethyl cellulose can reduce the surface energy of the membrane and also improve the hydrophobic properties of the membrane.
[0041] Therefore, the present invention modifies cotton fibers by using ethyl cellulose and aminated lignin. On the one hand, the hydrophobic properties of the membrane are improved by the joint modification of the two, thereby improving the separation efficiency of oil-water separation; on the other hand, the cotton fiber acts as a hydrogen bond donor and forms chemical interactions such as hydrogen bonds with ethyl cellulose to improve the adhesion of the hydrophobic layer on the cotton fiber substrate, thereby improving the mechanical properties of the separation membrane.
[0042] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0043] The experimental materials used in the embodiments of the present invention are all conventional experimental materials in the art and can be purchased through commercial channels.
[0044] Ethyl cellulose was purchased from Shanghai Aladdin Reagent Co., Ltd. (Shanghai, China) with a product number of E485978. The content of ethoxy groups in the ethyl cellulose was 48%.
[0045] Example 1: Preparation of oil-water separation membrane
[0046] (1) Dissolve 0.5 g of lignin in 25 mL of NaOH solution to obtain a lignin solution, wherein the pH of the NaOH solution is 11; add 1 g of ethylenediamine to the lignin solution to obtain a mixed solution, heat the mixed solution to 80°C and keep it warm, then add 0.5 mL of 37% formaldehyde solution dropwise to the mixed solution, react at 80°C for 0.5 h, precipitate the reaction product with 10% hydrochloric acid, and centrifuge to obtain aminated lignin;
[0047] 0.5 g of aminated lignin was dissolved in 25 mL of NaOH solution with a pH of 11 to obtain an aminated lignin solution. The cotton was washed with deionized water and ethanol in turn to remove dust and impurities on the surface. The washed cotton was then dried at 60°C. The dried cotton was completely immersed in the aminated lignin solution for 0.5 h, taken out and dried at 80°C to obtain lignin-modified cotton. The SEM electron microscope image of the prepared lignin-modified cotton is shown in FIG. Figure 1 As shown;
[0048] (2) Dissolve 0.1 g of ethyl cellulose in 10 mL of ethanol solution to obtain an ethyl cellulose solution, wherein the volume fraction of the ethanol solution is 75%. The modified lignin is completely immersed in the ethyl cellulose solution for 0.5 h, taken out and dried at 60°C to obtain an oil-water separation membrane. The SEM electron microscope image of the obtained oil-water separation membrane is as follows: Figure 1 shown.
[0049] Example 2: Preparation of oil-water separation membrane
[0050] (1) 0.3 g of lignin was dissolved in 25 mL of NaOH solution to obtain a lignin solution, wherein the pH of the NaOH solution was 10; 1 g of ethylenediamine was added to the lignin solution to obtain a mixed solution, the mixed solution was heated to 70°C and kept warm, and then 0.5 mL of a 35% formaldehyde solution was added dropwise to the mixed solution, and the mixture was reacted at 70°C for 0.6 h. The reaction product was precipitated with 10% hydrochloric acid and centrifuged to obtain aminated lignin;
[0051] 0.5 g of aminated lignin was dissolved in 20 mL of a NaOH solution with a pH of 11 to obtain an aminated lignin solution, cotton was washed with deionized water and ethanol in turn to remove dust and impurities on its surface, the washed cotton was dried at 50° C., the dried cotton was completely immersed in the aminated lignin solution for 0.3 h, and then taken out and dried at 50° C. to obtain lignin-modified cotton;
[0052] (2) Dissolve 0.05 g of ethyl cellulose in 10 mL of ethanol solution to obtain an ethyl cellulose solution, wherein the volume fraction of the ethanol solution is 75%. Soak the lignin-modified cotton completely in the ethyl cellulose solution for 0.3 h, and then take it out and dry it at 50°C.
[0053] Example 3: Preparation of oil-water separation membrane
[0054] (1) 0.6 g of lignin was dissolved in 25 mL of NaOH solution to obtain a lignin solution, wherein the pH of the NaOH solution was 11; 1 g of ethylenediamine was added to the lignin solution to obtain a mixed solution, the mixed solution was heated to 90°C and kept warm, and then 0.5 mL of a 40% formaldehyde solution was added dropwise to the mixed solution, and the mixture was reacted at 90°C for 0.3 h. The reaction product was precipitated with 10% hydrochloric acid and centrifuged to obtain aminated lignin;
[0055] (2) Dissolve 0.5 g of aminated lignin in 30 mL of NaOH solution with a pH of 11 to obtain an aminated lignin solution. Wash the cotton with deionized water and ethanol in turn to remove dust and impurities on its surface. Dry the washed cotton at 80°C. Soak the dried cotton in the aminated lignin solution for 0.6 h, take it out and dry it at 80°C to obtain an oil-water separation membrane.
[0056] (3) Dissolve 0.15 g of ethyl cellulose in 10 mL of ethanol solution to obtain an ethyl cellulose solution, wherein the volume fraction of the ethanol solution is 75%. The lignin-modified cotton is completely immersed in the ethyl cellulose solution for 0.5 h, taken out and dried at 80° C. to obtain an oil-water separation membrane.
[0057] Comparative Example 1:
[0058] Only aminated lignin is used to modify cotton fibers to obtain an oil-water separation membrane. The specific steps are:
[0059] (1) Dissolve 0.5 g of lignin in 25 mL of NaOH solution to obtain a lignin solution, wherein the pH of the NaOH solution is 11; add 1 g of ethylenediamine to the lignin solution to obtain a mixed solution, heat the mixed solution to 80°C and keep it warm, then add 0.5 mL of 37% formaldehyde solution dropwise to the mixed solution, react at 80°C for 0.5 h, precipitate the reaction product with 10% hydrochloric acid, and centrifuge to obtain aminated lignin;
[0060] 0.5 g of aminated lignin was dissolved in 25 mL of a NaOH solution with a pH of 11 to obtain an aminated lignin solution. The cotton was washed with deionized water and ethanol in turn to remove dust and impurities on its surface. The washed cotton was then dried at 60°C. The dried cotton was completely immersed in the aminated lignin solution for 0.5 h, taken out and dried at 80°C to obtain lignin-modified cotton as an oil-water separation membrane.
[0061] Comparative Example 2:
[0062] Only ethyl cellulose is used to modify cotton fiber to obtain an oil-water separation membrane. The specific steps are:
[0063] Dissolve 0.1 g of ethyl cellulose in 10 mL of ethanol solution to obtain an ethyl cellulose solution, wherein the volume fraction of the ethanol solution is 75%. Completely immerse cotton in the ethyl cellulose solution for 0.5 h, take it out and dry it at 60° C. to obtain an oil-water separation membrane.
[0064] Test Example 1: Oil-water separation test
[0065] 5 mL of chloroform and 5 mL of water were measured and mixed to obtain an oil-water mixture, wherein chloroform was dyed with methyl orange for the convenience of observation and calculation. A blank control group was set up, in which only cotton was used as a separation membrane. Equal amounts of separation membranes of Example 1, Comparative Examples 1-2 and the blank control group were respectively placed on the head of a syringe as a sieve, and the oil-water mixture was placed in a syringe for oil-water separation, and the separation time was controlled to be 5 s, and an oil-water separation test was performed. The results are shown in Table 1.
[0066] The calculation formula of oil-water separation efficiency is:
[0067] ;
[0068] In the formula, represents the volume of oil collected after separation, represents the initial oil volume.
[0069] Table 1 Separation efficiency of oil-water separation membrane for oil-water mixture
[0070]
[0071] Chloroform sinks to the bottom because its density is higher than that of water. Since it is stained by methyl orange, when the oil-water separation membrane prepared in Example 1 is placed in oily wastewater composed of chloroform and water, an obvious "silver mirror reaction" is observed in the water. The main reasons for this phenomenon are: the surface energy of the oil-water separation membrane is low, and water droplets cannot spread on its surface. At the same time, due to the modification of micro-nano particles on the surface of the oil-water separation membrane, air "cushions" are filled between the particles, which provides support for hydrophobicity. When the oil-water separation membrane contacts chloroform, chloroform will be adsorbed and the oily wastewater will be restored to a clear state.
[0072] It can be seen from Table 1 that the separation efficiency of the oil-water separation membrane prepared by the present invention for chloroform and water in oily wastewater can reach 98.34%. The oil-water separation efficiency of the separation membrane prepared by using only aminated lignin to modify cotton is 23.4%, and the oil-water separation efficiency of the separation membrane prepared by using only ethyl cellulose to modify cotton is 56.7%. It can be seen that the oil-water separation membrane prepared by the present invention uses ethyl cellulose and aminated lignin to modify cotton in combination, which has a synergistic effect in improving the separation efficiency of the separation membrane in oil-water separation.
[0073] Test Example 2: Adsorption capacity test
[0074] The oil-water separation membrane prepared in Example 1 was tested for adsorption capacity of different types of oils and fats. The results are shown in Table 2.
[0075] Take a certain mass of separation membrane and weigh it as The separation membrane was immersed in different organic solvents and oils for 3 minutes until saturation, and then the excess oil was removed and weighed immediately. , the adsorption amount of oil-water separation membrane for different types of oil was calculated, and the results are shown in Table 2.
[0076] The calculation formula of adsorption amount is:
[0077] ;
[0078] In the formula, Indicates the weight of the separation membrane that has adsorbed oil to saturation. Indicates the weight of the separation membrane in the initial state.
[0079] Table 2 Adsorption of different oils and fats by the oil-water separation membrane prepared in Example 1
[0080]
[0081] Different oils and fats have different densities, resulting in different adsorption capacities of the same oil-water separation membrane. As can be seen from Table 2, the oil-water separation membrane prepared by the present invention has the weakest adsorption capacity for n-butane, with an adsorption capacity of 11.6 g / g, and the strongest adsorption capacity for soybean oil, with an adsorption capacity of 23.7 g / g.
[0082] Test Example 3: Cyclic Performance Test
[0083] 1. Changes in wettability of oil-water separation membrane after circulation
[0084] The oil-water separation membrane prepared in Example 1 was subjected to 50 oil-water separation tests. The cyclic performance of the oil-water separation membrane was reflected by detecting the change in contact angle during the 50 cyclic separation tests. The results are as follows: Figure 1 shown.
[0085] The specific test steps are as follows: the same as the test method in Test Example 1, the oil-water separation membrane is placed on the head of the syringe as a screen, the oil-water mixture is placed in the syringe for oil-water separation, the separation time is controlled to be 5s, and the oil-water separation test is performed. The oil-water separation is a mixture of chloroform and water in a volume ratio of 1:1. In order to study the recyclability of the coated fabric, the oil-water separation process is repeated 50 times, and after each separation process, the separation membrane is physically squeezed and dried for further use.
[0086] Depend on Figure 1 It can be seen that after 50 cycles of testing, the contact angle of the oil-water separation membrane prepared in Example 1 decreased from 143.4° to 142°, and the contact angle was reduced by only 0.98%. Therefore, after 50 cycles of use, the oil-water separation membrane prepared in the present invention still maintains good separation performance.
[0087] 2. Changes in separation efficiency of chloroform / water mixture system after circulation
[0088] The oil-water separation membrane prepared in Example 1 was subjected to 10 oil-water separation tests. The specific test steps were the same as those in Test Example 1. After each separation process, the separation membrane was physically squeezed and dried for further use. The separation efficiency before and after the cycle was tested to determine the cycle performance of the oil-water separation membrane. The results are shown in FIG. Figure 2 shown.
[0089] Depend on Figure 2 It can be seen that after 10 cycles of testing, the separation efficiency of the oil-water separation membrane prepared in Example 1 decreased from 98.34% to 97%, and the separation efficiency only decreased by 1.36%. Therefore, after 10 cycles of use, the oil-water separation membrane prepared by the present invention still maintains good super oleophilic selective wettability and has a good separation effect on oil-water mixtures.
[0090] The above description is only the preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing an oil-water separation membrane, characterized in that: The following steps are involved: (1) The aminated lignin and the alkaline solution are mixed at a solid-liquid ratio of 0.5 g: (20-30) mL to obtain an aminated lignin solution; the pretreated cotton substrate is soaked in the aminated lignin solution for 0.3-0.6 h, and then dried at 50-80° C. to obtain lignin-modified cotton; The preparation method of aminated lignin is as follows: lignin and NaOH solution are mixed at a solid-liquid ratio of (0.3-0.6) g: 25 mL to obtain a lignin solution; ethylenediamine is added to the lignin solution to obtain a mixed solution, the mixed solution is heated to 70-90° C. and kept warm, and then a formaldehyde solution is added to the mixed solution, and after reacting at 70-90° C. for 0.3-0.6 h, the reaction product is precipitated with hydrochloric acid to obtain aminated lignin; wherein the solid-liquid ratio of lignin, ethylenediamine and formaldehyde solution is (0.3-0.6) g: 1 g: 0.5 mL; The alkaline solution is a NaOH solution, the pH of the NaOH solution is 10-11; (2) Ethyl cellulose and ethanol solution are mixed at a solid-liquid ratio of (0.05-015) g:10 mL to obtain an ethyl cellulose solution; the lignin-modified cotton is soaked in the ethyl cellulose solution for 0.3-0.6 h, and then dried at 50-80° C. to obtain an oil-water separation membrane.
2. The method for preparing an oil-water separation membrane according to claim 1, characterized in that: In step (1), the cotton substrate is pretreated by washing the cotton substrate with deionized water and ethanol in sequence to remove dust and impurities on its surface, and then drying the washed cotton substrate at 50-80°C.
3. The oil-water separation membrane prepared by the preparation method according to claim 1 or 2.
4. Use of the oil-water separation membrane obtained in claim 3 in separating oily wastewater.
5. The use according to claim 4, characterized in that The oil in the oily wastewater is one or more of n-butane, chloroform, soybean oil or olive oil.
